Possibilities of Applying Qualitative Research Methods During the Measurement of Health Behavior in Adolescents (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
A number of international research was made in the recent years to explore the health behavior of adolescents, most of them supported health behavior indicators with statistical data by applying quantitative research methods. Only a few researches volunteered to explore deeper correlations of health behavior with the help of qualitative tools. It is a feature of quantitative studies that specific phenomena appear as quantified, "coded" clusters of statistical data, from which apparently valid generalizations and trends emerge. Individual manifestations, along with those important aspects of phenomena that are personally important from the point of the individuals, giving the essence of relation systems which establish social processes remain hidden. Consequently, the researcher is unable to reveal the depths of the tested phenomenon only indicate trends. However, the qualitative methodology by exploring individual perspectives may result in the understanding of deeper correlations which may contribute to a more nuanced interpretation of the observed phenomena. When examining the health behavior of adolescents the use of qualitative tools may be the income of the knowledge of visible life parameters, the value attitude concerning health, motivation to choose healthy/unhealthy and thinking structures.